Litigation and non-litigation approaches in Islamic Banking Syariah resolution - Amda Usnaka (Goodwood Publishing, 2025)
Purpose: This study aims to analyze dispute resolution mechanisms in Islamic banking in Indonesia, focusing on mudharabah contract disputes. It examines the role of litigation through the Religious Court and non-litigation through alternative dispute resolution institutions, particularly the National Sharia Arbitration Board (BASYARNAS), in maintaining Sharia compliance and legal certainty. Research Methodology: This study adopts a normative juridical approach, analyzing statutory regulations such as Law No. 21 of 2008 on Sharia Banking, complemented by a literature review and doctrinal interpretation. A qualitative method is used to assess the legal frameworks and institutional practices in resolving Islamic banking disputes. Results: Findings indicate that both litigation and non-litigation mechanisms are legally recognized and essential for upholding Sharia principles, ensuring fairness, and fostering trust among stakeholders in Islamic banking. Litigation provides authoritative judicial decisions, whereas non-litigation offers efficiency, confidentiality, and flexibility in resolving disputes. Conclusions: The dual dispute resolution framework strengthens Islamic banking governance in Indonesia. However, its effectiveness depends on the synergy between financial institutions, regulators, and dispute resolution bodies, as well as the enhancement of institutional capacity and public awareness. Limitations: This study is limited to legal and institutional analyses without empirical data from case studies, which may restrict insights into real-world challenges and stakeholder perspectives. Contribution: This study contributes to the discourse on sharia-based dispute resolution by providing recommendations for improving the effectiveness, accessibility, and fairness of both litigation and non-litigation processes in Islamic banking.